2010
DOI: 10.2522/ptj.20090388
|View full text |Cite
|
Sign up to set email alerts
|

Family Priorities for Activity and Participation of Children and Youth With Cerebral Palsy

Abstract: Parents' priorities for their children and youth with cerebral palsy differed depending on age and gross motor function level; however, the most frequent priority for all age groups was daily activities. Interviews with families are recommended for identifying outcomes for activity and participation and developing an intervention plan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
80
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 20 publications
10
80
0
4
Order By: Relevance
“…5,10 Others stated that the majority of research assistants were health care professionals experienced in complication during collection of data because of child's communication. 9 Other studies described that poor parent-child communication increased the risk of psychosocial problems in school-aged children. 21 Others recommended that the speech therapy aims at improving communication.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5,10 Others stated that the majority of research assistants were health care professionals experienced in complication during collection of data because of child's communication. 9 Other studies described that poor parent-child communication increased the risk of psychosocial problems in school-aged children. 21 Others recommended that the speech therapy aims at improving communication.…”
Section: Resultsmentioning
confidence: 99%
“…20 Others stated a self-feeding and nutrition was concerns of families of young children and children with severe motor limitations and could reflect parents' concern for their children's growth, dental care, skin care and general health status. 9 Altered smooth muscle and sphincter tone together with the effects of medications, diminished activity, and variable hydration contribute to the high incidence of constipation in children with CP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For many parents of preschool-age children, priorities often include optimizing their child's self-care and mobility abilities, with school performance only becoming a priority as children reach school age. 32 Our study has shown that preschool-age children with CP already have substantial deficits in multiple development areas beyond mobility and self-care, 33 including communication and social competence. If readiness-to-learn skills are not considered until children reach school age, those with CP may be further behind their peers with typical development and less likely to optimize their educational potential.…”
Section: Discussionmentioning
confidence: 99%
“…This initiative allows early intervention funding of up to AUD12 000 for children aged up to 7 years with a qualifying disability (including CP). 32 Parents can choose to allocate this funding to services of their choice. For many parents of preschool-age children, priorities often include optimizing their child's self-care and mobility abilities, with school performance only becoming a priority as children reach school age.…”
Section: Discussionmentioning
confidence: 99%